2010
DOI: 10.1111/j.1748-3743.2009.00196.x
|View full text |Cite
|
Sign up to set email alerts
|

Student nurses’ perception and understanding of elder abuse

Abstract: The findings provide useful information from which more comprehensive content about elder abuse can be developed in the gerontological nursing curriculum, to better prepare future nurses by increasing their basic understanding of elder abuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
(13 reference statements)
1
7
0
1
Order By: Relevance
“…However, a lack of practical training on elder abuse and neglect has been recognized as an obstacle. 41 As has been suggested in different studies, [41][42][43] it's going to be necessary to provide more comprehensive content on elder abuse within the medical and nursing student's program to better prepare future students by enhancing their basic perception and knowledge of elder abuse. Considering the effect of communication skills and attachment style on students' perceptions of elder abuse, individual characteristics should be included in future planning.…”
Section: Resultsmentioning
confidence: 99%
“…However, a lack of practical training on elder abuse and neglect has been recognized as an obstacle. 41 As has been suggested in different studies, [41][42][43] it's going to be necessary to provide more comprehensive content on elder abuse within the medical and nursing student's program to better prepare future students by enhancing their basic perception and knowledge of elder abuse. Considering the effect of communication skills and attachment style on students' perceptions of elder abuse, individual characteristics should be included in future planning.…”
Section: Resultsmentioning
confidence: 99%
“…Thomson et al [19] found that among UK specialists registrars in Geriatric Medicine, 74.1 % felt inadequately prepared to deal with case of elder abuse, and Lo et al [20] showed that nurses-to-be did not find themselves adequately prepared to fulfill this responsibility, concluding that more comprehensive content about elder abuse can be developed in the gerontological nursing curriculum.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, these items achieved a high I-CVI score of .99. A study conducted by Lo, Lai, and Tsui (2010) to elicit the perception, knowledge, and awareness of student nurses regarding elder abuse suggests that students recognize both physical and psychological abuse as behaviors denoting elder abuse. The results of this study also support this finding.…”
Section: Discussionmentioning
confidence: 99%